The Influence of The Halal Logo on Purchase Decisions of 7-Eleven Ready-To-Eat Food by Bangkok Muslims, Moderated by Primary Needs in The Perspective of Islamic Business - Hana Rolisa; Muhammad Iqbal; Yeni Susanti (Eduvest - Journal of Universal Studies, 2024)
This study examines the impact of the halal logo on the purchase decisions of 7-Eleven ready-to-eat food among Bangkok Muslims, moderated by primary needs from an Islamic business perspective. The halal logo is a certification label written in Arabic to indicate whether a product complies with Islamic law. This descriptive quantitative research involved 100 Muslim consumers of 7-Eleven ready-to-eat food in Bangkok, selected through purposive sampling. Data was collected using questionnaires and analyzed with SEM-PLS. The findings reveal that the halal logo significantly and positively influences purchase decisions among Bangkok Muslims. Moreover, primary needs positively and significantly affect these decisions and serve as a moderating factor in the relationship between the halal logo and purchase decisions. The study underscores the importance of the halal logo in guiding Muslim consumers' purchase behavior and highlights the role of primary needs in strengthening this effect. These insights aim to encourage the Muslim community in Bangkok to prioritize halal-certified products, thereby boosting the sales volume of halal food in the region. The findings also provide valuable implications for businesses to enhance their marketing strategies for halal products in Bangkok, Thailand.